Perinatal outcome of meconium stained amniotic fluid in pregnancy beyond 37 weeks - Suyajna, Joshi D.; G., Jayasakthi; Rai, Rajeswari; Banu, Ruksar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To identify the frequency of meconium aspiration syndrome among the total births who suffered from meconium staining of amniotic fluid, to find out risk factors during pregnancy, therapies and various complications associated with this condition and their effects on perinatal outcome. Methods: This was a retrospective study of 252 antenatal patients delivered at Department of DNB-OBG District hospital Bellary during the year January 2019 to December 2019 with gestational age between 37-40 weeks with singleton pregnancies and cephalic presentation were included in the study. Results: The Caesarean section rate for fetal distress was 96.6% in patients with meconium stained amniotic fluid (MSAF). Meconium aspiration syndrome (MAS) was found in3.93% babies. APGAR score at 1 minute <7 was found in 25 cases (9.84%). Conclusions: Meconium stained amniotic fluid is associated with increased need for neonatal resuscitation, increased risk of birth asphyxia, meconium aspiration syndrome, hospital admission and mortality. So identification of pregnant woman at risk of passage of meconium during labour would allow intensive fetal surveillance and early intervention which might lead to reduction in neonatal adverse outcome.